A review of tourism and climate change mitigation: The scales, scopes, stakeholders and strategies of carbon management. (April 2023) - Gössling, Stefan; Balas, Martin; Mayer, Marius; Sun, Ya-Yen
Abstract: Tourism needs to reduce emissions in line with other economic sectors, if the international community's objective of staying global warming at 1.5°-2.0 °C is to be achieved. This will require the industry to half emissions to 2030, and to reach net-zero by mid-century. Mitigation requires consideration of four dimensions, the Scales, Scopes, Stakeholders and Strategies of carbon management. The paper provides a systematic review of these dimensions and their interrelationships, with a focus on emission inventory comprehensiveness; allocation principles at different scales; clearly defined responsibilities for decarbonization; and the identification of significant mitigation strategies. The paper concludes that without mitigation efforts, tourism will deplete 40% of the world's remaining carbon budget to 1.5 °C. Yet, the most powerful decarbonization measures face major corporate, political and technical barriers. Without worldwide policy efforts at the national scale to manage the sector's emissions, tourism will turn into one of the major drivers of climate change.